Postmodern Consumerism and the Construction of Self in Han Kang’s The Vegetarian - Adhikari, Tej Narayan; Pokharel, Bishnu Prasad (The Outlook: Journal of English Studies, 2025)
This paper critically examines Han Kang’s The Vegetarian, focusing on the protagonist Yeong-hye’s radical transformation and its implications within capitalist and patriarchal structures. Employing Karl Marx’s concept of commodity fetishism and Fredric Jameson’s theory of postmodern consumer culture, the study explores how Yeong-hye’s rejection of meat consumption symbolizes resistance against commodification and societal norms. Her metamorphosis into a plant-like state reflects a profound alienation from a society that objectifies individuals, particularly women, reducing them to consumable entities. This transformation challenges traditional notions of identity and autonomy, highlighting the dehumanizing effects of consumer capitalism. However, the analysis problematizes the efficacy of Yeonghye’s resistance, considering whether her withdrawal signifies empowerment or a retreat into passivity. In the end, it suggests that personal freedom matters more to a person than following traditions in a consumer-driven society. Ultimately, it implies that individual autonomy is more important for an individual than tradition in consumer culture.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />